2005
DOI: 10.1177/107424840501000309
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Oral Magnesium in a Patient With Ventricular Tachycardia Due to Hypomagnesemia

Abstract: A 12-year-old girl with occasional symptoms of chest discomfort was diagnosed with ventricular tachycardia on cardiac evaluation. No evidence of organic heart disease was apparent, but a laboratory evaluation revealed hypomagnesemia. Ventricular tachycardia disappeared after treatment with 200 mg/day of oral magnesium hydroxide, and no further chest discomfort was reported. In addition to routine cardiac evaluation for arrhythmia, serum magnesium levels should be checked in patients with suspected idiopathic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…While the cardiac evaluation for arrhythmia was normal, the Mg 2+ serum level was low. Oral supplementation with magnesium effectively suppressed both PVCs and the episodes of ventricular tachycardia, documented over a follow-up of 5 years [ 82 ].…”
Section: Cardiovascular Importance Of Magnesiummentioning
confidence: 99%
“…While the cardiac evaluation for arrhythmia was normal, the Mg 2+ serum level was low. Oral supplementation with magnesium effectively suppressed both PVCs and the episodes of ventricular tachycardia, documented over a follow-up of 5 years [ 82 ].…”
Section: Cardiovascular Importance Of Magnesiummentioning
confidence: 99%
“…2+ are used for the treatment of digitalis intoxication, vasospastic angina pectoris, and arrhythmias. Correction of Mg 2+ deficiency (MD) eliminates rhythm disturbances in parenteral and/or peroral administration of Mg 2+ salts.The effect of various Mg 2+ compounds such as Mg(OH) 2 , MgO, MgSO 4 was evaluated in numerous experimental and clinical studies [4,7,8]. Holter monitoring showed that the incidence of ventricular and atrial arrhythmias in individuals with low blood Mg 2+ content caused by insufficient alimentary Mg 2+ intake is higher than in the group with normal Mg 2+ content [6].…”
mentioning
confidence: 99%